Endo-Aortic vs. Trans-Thoracic Clamping in Right Mini-Thoracotomy Mitral Valve Surgery: Outcome on Myocardial Protection - Barbero, Cristina; Rinaldi, Mauro; Pocar, Marco; Cura Stura, Erik; Calia, Claudia; Sebastiano, Viviana; Marchetto, Giovanni; Filippini, Claudia; Boffini, Massimo; Ricci, Davide (Frontiers in Cardiovascular Medicine, 2021)
Background: Perfusion strategies and aortic clamping techniques for right mini-thoracotomy mitral valve (MV) surgery have evolved over time and remarkable short- and long-term results have been reported. However, some concerns have raised about the adequacy of myocardial protection during the minimally invasive approach, particularly with the endo-aortic clamp (EAC). Aim of this study was to compare the efficacy, in terms of myocardial preservation, of the EAC with the trans-thoracic aortic clamp (TTC) in patients undergoing right mini-thoracotomy MV surgery. Methods: A single center, prospective observational study was performed on patients undergoing right mini-thoracotomy MV surgery with retrograde arterial perfusion and EAC or TTC. A propensity matched analysis was performed to compare the two groups. Primary outcome was the comparison between cardiac troponin T levels measured at different time-points after surgery. Results: Eighty EAC patients were compared with 37 TTC patients. No cases of myocardial infarction or low cardiac-output syndrome were overall reported. No differences were recorded in terms of stroke, peri-operative mortality, and in the release of myocardial markers, lactates levels and need for inotropic support at different time-points after surgery. CK-MB peak levels were significantly lower in the EAC group. Conclusion: Despite concerns arising about the EAC, this prospective study shows equivalence in terms of myocardial preservation of the EAC compared with the TTC in patients undergoing right mini-thoracotomy MV surgery.